Beginning Teachers Improve Classroom Practice Through Collaborative Inquiry - Barbara H. Davis; Virginia Resta; Karen Miller; Keitha Fortman (Networks: An Online Journal for Teacher Research, 1999)
"How can I get my students to pay attention to me?" "What will motivate my reluctant readers to read more?" "How can I get my students to work together in cooperative groups?" "Would teaching social skills improve discipline in my classroom?" "How can I get my students to stay on-task and become more productive?" "What can I do to get my at-risk students to produce quality work?" These questions, and others like them, are asked by classroom teachers every year, especially beginning teachers who are encountering the challenges of the classroom for the first time. In recent years many teachers have discovered that action research is an effective method for seeking answers to questions that are relevant to their classrooms.